1H-Pyrazolo[3, 4-g]hexahydro-isoquinolines as potent GR antagonists with reduced hERG inhibition and an improved pharmacokinetic profile. Issue 24 (15th December 2015) - Hunt, Hazel J.; Belanoff, Joseph K.; Golding, Emily; Gourdet, Benoit; Phillips, Timothy; Swift, Denise; Thomas, Jennifer; Unitt, John F.; Walters, Iain
Graphical abstract: Abstract: We report the further optimization of our series 1 H -pyrazolo[3, 4- g ]hexahydro-isoquinoline sulfonamides as GR antagonists. By incorporating a heteroaryl ketone group at the ring junction, we have obtained compounds with excellent functional GR antagonism. Optimization of the sulfonamide substituent has provided compounds with a very desirable overall profile, including minimal hERG activity, good bioavailability and in vivo efficacy.